Infodemi COVID-19 dengan Peran Social Media Fatigue, Deficient Self-Regulation, dan Promosi Diri - Nada Sandvika Triyono (Universitas Bina Sarana Informatika, 2022)
Social media envelopes a tremendous impact on the spread of the COVID-19 virus information. Nevertheless, this also increases the probability of misinformation-spreading as well. Using the affordace theory as well as the cognitive load theory, this study aims to analyze the effects of social media fatigue (SMF), deficient self-regulation (DS-R), and self-promotion on the spread of the COVID-19 misinformation on social media. The population of this research includes Indonesian social media users in the age range of 18 to 24 years old, with a number of sample N=155 (retrieved from G*power software). We use the Likert scale for our questionnaire, and the convenience sampling method for our study, spreading the questionnaire through online platforms such as LINE, WhatsApp, and Instagram. The data will then be analyzed using the SPSS software. Keywords: misinformation, social media, COVID-19